Real-life functioning in women with schizophrenia living in residential facilities: Gender-based comparison - Rusakovskaya, Olga; Kharitonova, Natalia; Movina, Larisa; Papsuev, Oleg (Frontiers in Psychiatry, 2023)
Introduction Despite many patients with schizophrenia being able to achieve good functional outcomes, the number of patients with poor functional outcome estimates at over 25 percent. One of the wider constructs, reflecting functional outcomes in schizophrenia, is real-life functioning, whose key domains include ability to live relatively autonomously, productive activity and social interaction. Negative symptoms are seen among independent predictors of real-life functioning. As most researchers agree that schizophrenia is a disease with gender differences in terms of both clinical and functional outcomes, the goal of our observational study was to examine real-life functioning of women with schizophrenia, living in residential care facilities, and study the relationship between daily functioning and negative symptoms. Methods Using the Standardized Protocol of Clinical Interview and observation for 1 or more weeks, we examined 46 females with schizophrenia, living in psychiatric residential facilities and compared them with 54 males with schizophrenia, living in the same facilities. In a pilot study 21 subjects with schizophrenia (13 females and 8 males), were evaluated by the Russian version of the Brief Negative Symptom Scale (BNSS). Results To the results, more females with schizophrenia, compared to males with schizophrenia, remained active and took initiative in their physical care, vocational activities, involvement in cultural events, and maintained friendly relationships with other inmates. We have identified a group of inmates, in which females prevailed, with less pronounced negative symptoms and a higher level of social functioning, who did not need residential social care in the institutions. Discussion Limitations of residential social care in the institutions for psychiatric patients are discussed.